Nonfragile stabilization for semi‐Markovian switching systems with actuator saturation via improved dynamic event‐triggered scheme - Luo, Miaohong; Wu, Xihui; Mu, Xiaowu; Yang, Zhe (International journal of robust and nonlinear control, 2021)
This article addresses the problem of stabilization and the H∞ performance for semi‐Markovian systems with actuator saturation via dynamic event‐triggered scheme. Due to actuator degradation and numerical round‐off errors, nonfragile control is proposed. Meanwhile, the saturated nonlinearity is considered in the controller design process, which makes the controller design more practical. Furthermore, the improved event‐triggered scheme is utilized for reducing transmitting unnecessary sampled data to the network and saving communication cost. By establishing appropriate Lyapunov–Krasovskii functional that depends on model information and using free‐weighting matrix techniques, new sufficient conditions for ensuring the stabilization of the controlled systems are obtained. Then the gain matrices of the controller can be also designed. Finally, simulation examples are provided to verify that the results we get are effective.